2016
DOI: 10.1002/jbm.a.35647
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells and alginate microcarriers for craniofacial bone tissue engineering: A review

Abstract: Craniofacial bone is a complex structure with an intricate anatomical and physiological architecture. The defects that exist in this region therefore require a precise control of osteogenesis in their reconstruction. Unlike traditional surgical intervention, tissue engineering techniques mediate bone development with limited postoperative risk and cost. Alginate stands as the premier polymer in bone repair because of its mild ionotropic gelation and excellent biocompatibility, biodegradability, and injectabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 116 publications
0
32
0
Order By: Relevance
“… 1 4 Although abundant efforts have been devoted to develop bone mimic materials, ideal scaffolds which are osteoinductive, biocompatible, and induce effective bone in-growth at the repair sites are still lacking. 3 , 10 , 11 , 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“… 1 4 Although abundant efforts have been devoted to develop bone mimic materials, ideal scaffolds which are osteoinductive, biocompatible, and induce effective bone in-growth at the repair sites are still lacking. 3 , 10 , 11 , 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…These pre-osteoblasts (such as the ST2 cells utilized in this study) are then able to differentiate into osteoblasts based on their extracellular matrix environment should they receive the appropriate cues to fully differentiate into mature bone-forming osteoblasts [28,29,30]. Noteworthy, BMPs in general have played an important role in regulating the tissue pool of pre-osteoblasts and help to significantly induce their subsequent differentiation towards producing mature bone [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…More recent research has shown that a variety of hydrogels and nanogels are able to serve as ideal scaffolds for tissue regeneration by either carrying live progenitor cells or growth factors within their matrix [30,37,38,39,40]. Furthermore, the properties of various gel-like biomaterials, such as a the cross-linked gel carrier system utilized in this study, are able to facilitate new bone formation as quantified either in vitro or in vivo [21,22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, large bone defects and fractures represent an increasing clinical challenge, most of which are treated using either autograft or allograft bone tissues . However, both of these treatments have many drawbacks that limit their application such as the immunological rejection and disease transmission . Compared to autografts and allografts, bone tissue engineering (BTE) has a higher osteogenic activity, less trauma, and lower immunogenicity …”
Section: Introductionmentioning
confidence: 99%
“…1 However, both of these treatments have many drawbacks that limit their application such as the immunological rejection and disease transmission. 2 Compared to autografts and allografts, bone tissue engineering (BTE) has a higher osteogenic activity, less trauma, and lower immunogenicity. 3 Traditional BTE strategies are applied using a top-down (TD) approach, in which high density of seed cells are directly dropped on three-dimensional (3D) scaffolds with porous structures and cultured in petri dishes for osteodifferentiation.…”
Section: Introductionmentioning
confidence: 99%